Evaluasi Kebergunaan dan Pembangunan Website Online Library Information System Menggunakan Think Aloud - Simbolon, Iustisia; Simanjuntak, Riski Yan Daniel; Siregar, Edrei Abiel Benaya (Jurnal Teknik Informatika dan Sistem Informasi, 2025)
Usability refers to the quality of the user experience when interacting with a product or system, including websites, software, devices or applications. Usability is about effectiveness, efficiency and overall user satisfaction. OLIS (Online Library Information System) is an information system that functions as a catalog for managing the Del Institute of Technology library. Based on the usability value measurement results, the OLIS website has an SUS value of 41.25 or a “poor” level of usability. This shows that the usability aspect of the website must be improved. To achieve good usability, a usability evaluation is carried out using the think aloud method. This evaluation is carried out for at least 2 iterations until the OLIS usability value reaches a minimum value of 80. The results of the first iteration evaluation are 18 problem findings which are then analyzed to make the first iteration improvement design. Furthermore, the second iteration identifies problems from the first evaluation and produces 17 usability problems which will then be analyzed to make a second iteration improvement design that will be made into the final high fidelity prototype. The SUS measurement results on the OLIS website which have been evaluated by think aloud is 85.25 or the usability level is "excellent".